Survey of LEU olympiad 2014 for young mathematicians - Gesevičienė, Vilma; Mazėtis, Edmundas; Jakaitytė, Eglė (Lietuvos matematikos rinkinys, 2015)
The texts and solutions of the LEU young mathematicians olympiad – 2015 are presented.
Keywords: mathematical olympiads; problem solving